(untitled) (Revista Nacional de Odontología, 2019)
Objective: To analyze the prevalence of signs and symptoms related to stress, depression/anxiety and poor mental health and its association with sociodemographic factors in undergraduate students of the Faculty of Dentistry of the University of Antioquia. Methods: A cross-sectional study was conducted by means of a survey in 205 students (104 women). Variables: sociodemographic, general health, mental health (GHQ-12), depression/anxiety (Zung test), self-perceived stress. Analyses were carried out by sex, by means of a description of variables and crude and adjusted Odds ratio with 95% confidence intervals (aOR- 95%CI) was calculated, by logistic regression, in order to estimate association between variables. Results: Prevalence of indicators for men and women were the following (in order): poor mental health 43% and 52%, depression/anxiety 42% and 50% and self-perceived stress 34% and 41% (higher percentages in women). Significant statistically associations were found for men reporting depression/anxiety and stress and low social support (OR 20.94; 95%CI 2.13- 205.81 and OR 5.04; 95%CI 1.01- 25.02 respectively). Also, men and women proceeding from extended-assembled families were more likely to report depression/anxiety (OR: 8.82; 95%CI 1.29- 60.17 and OR: 14.94; 95%CI 1.56- 143.15 respectively). Women reporting low social support were more likely to report poor mental health, depression/anxiety and stress (OR: 20.72; 95%CI 2.19- 195.73; OR: 15.61; 95%CI 1.68- 144.62 y OR: 30.61; 95%CI 3,08- 304,35 respectively). Conclusions: Higher prevalence of signs and symptoms that suggest poor mental health, and differences according to sex and sociodemographic characteristics were found.